A Case of True Hermaphroditism Presenting as a Testicular Tumour. (3rd February 2015) - Ceci, Michelle; Calleja, Edward; Said, Edith; Gatt, Noel
Abstract : True hermaphroditism represents only 5% cases of all of disorders of sexual differentiation (DSD) and usually present in early childhood with ambiguous genitalia. Occasionally, cases might present later on in adolescence with problems of sexual maturation. Our case report presents a true hermaphrodite with normal male phenotype that presented as a left testicular mass, two years after being diagnosed with Sertoli cell only syndrome in the contralateral testis. Histological examination of the left testis showed ovarian, fallopian tube, myometrial, endometrial, and epididymal tissue. This combination of findings is found in approximately one-third of true hermaphrodites, but it is very rare to present clinically as an inguinoscrotal mass.